PPGIS mapping of landscape values and development preferences in the greater Kuala Lumpur - Teh, Mun Jun (2021)
Unplanned and poorly managed urbanisation can give rise to pollution, inequity, impacts on ecosystem services and reduced liveability. The objective of this study is to identify, map and compare residents' landscape values and development preferences using Public Participatory GIS to provide place-specific recommendations for urban planning in Kuala Lumpur. The study compares a range of landscape values and development preferences to assess conflict and compatibility. Landscape values represent valued landscape typologies such as aesthetic and spiritual locations, while development preferences represent participants’ preference on whether a location should be developed or conserved. A conceptual model of compatibility and conflict is used to consider the relationship between development preferences and landscape values in two dimensions. Conflict emerges in areas where there is disagreement between landscape values and development preference such in areas recognized for its biodiversity and identified for development. Using a web-based PPGIS social survey, 249 respondents were surveyed across Greater Kuala Lumpur. Our mapping found most of the locations identified were in Kuala Lumpur, Petaling Jaya, Shah Alam, Klang and Kajang. Landscape values which support conservation were generally found in areas with compatible development preferences. The results suggest the participants identified locations for pro-environmental development which were compatible with landscape values, mainly in the forested areas surrounding Kuala Lumpur city; but there were also areas of conflict, mainly inside Kuala Lumpur city regarding pro-development preferences and landscape values. The results of this study potentially provide a pathway forward for supporting urban development that is sustainable and also accounts for community interests.